2020
DOI: 10.1177/0972150920919875
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing good Corporate Governance Mechanism to Improve Performance: Case in Indonesia’s Manufacturing Companies

Abstract: The application of good corporate governance (GCG) aims to improve company performance. In implementing GCG, a mechanism is needed, namely a procedure and a clear relationship between the decision-maker and the party overseeing the decision. The mechanism of GCG can be measured by the numbers of board of directors, independent board of commissioners, audit committees, and also managerial ownership. This research is conducted at manufacturing companies listed on the Indonesia Stock Exchange, with a total sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Independent commissioners play a critical role in establishing good CG. The term “independent” in relation to the post of independent commissioner refers to the idea that an independent commissioner’s duties and obligations are carried out freely and without coercion from interested parties (Napitupulu et al , 2020). An independent commissioner, such as an independent director, has no particular relationships with other internal parties in the company, hence he is considered as decreasing the risk of agency conflict between top management and shareholders to cut agency costs (Naciti, 2019; Al-Matari, 2020).…”
Section: Theoretical Review and Hypotheses Developmentmentioning
confidence: 99%
“…Independent commissioners play a critical role in establishing good CG. The term “independent” in relation to the post of independent commissioner refers to the idea that an independent commissioner’s duties and obligations are carried out freely and without coercion from interested parties (Napitupulu et al , 2020). An independent commissioner, such as an independent director, has no particular relationships with other internal parties in the company, hence he is considered as decreasing the risk of agency conflict between top management and shareholders to cut agency costs (Naciti, 2019; Al-Matari, 2020).…”
Section: Theoretical Review and Hypotheses Developmentmentioning
confidence: 99%
“…According to agency theory, the small size of the board of directors can guarantee good oversight thereby reducing the occurrence of tax evasion while the large size of the board of directors results in large tax evasion (Jensen and Meckling, 1978) Agency theory assesses that the greater the number of independent commissioners, the higher their influence in monitoring management performance (Arianti, 2020). Meanwhile, from the stakeholder theory, the existence of an independent board of commissioners will supporting GCG principles and the functioning of an independent board of commissioners will safeguard the interests of parties with an interest in the company (Napitupulu et al, 2020). This research is supported by Wijayanti and Merkusiwati (2017) and Honggo and Marlinah (2019) showing that independent commissioners have a negative effect on tax evasion.…”
Section: Hypothesis Development 161 Effect Of the Bord Of Directors O...mentioning
confidence: 99%
“…Literature has shown that greater board independence can lead to better performance. Napitupulu et al (2020), analyzing 52 listed companies in Indonesia, concluded that company performance, as measured by ROA, is improved by a board of directors with independent members to provide guidance and supervision for the company management. Also, Ben Barka and Legendre (2017) and Liu et al (2015) point out a positive relationship between the board’s independence and the company’s performance measured by ROE and ROA.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%